Dynamic controlled atmosphere for prevention of internal browning disorders in 'Rocha' pear. (January 2016) - Deuchande, Teresa; Carvalho, Susana M.P.; Guterres, Umbelina; Fidalgo, Fernanda; Isidoro, Nelson; Larrigaudière, Christian; Vasconcelos, Marta W.
Abstract: This study aimed to evaluate the potential of two dynamic controlled atmospheres, DCA-CF (chlorophyll fluorescence sensor) and DCA-EtOH (ethanol sensor) when compared to controlled atmosphere (CA), in the prevention of internal browning disorders (IBD) in 'Rocha' pear stored under commercial conditions. Pears harvested at optimal maturity were stored for 145 days at −0.5 °C and 95% relative humidity, under three atmospheres: (1) CA (3 kPa O2 + 0.5 kPa CO2 ), (2) DCA-CF and (3) DCA-EtOH. At the end of storage, fruits in DCA-CF did not develop IBD while fruits in DCA-EtOH had an IBD incidence of 15 and 20% after 125 and 145 days of storage, respectively. The higher incidence of IBD under DCA-EtOH may be related to the higher levels of fermentative metabolites and to the lower ascorbate content. In contrast, the higher levels of ascorbate in DCA-CF showed that this technology contributes to maintaining the fruit's antioxidant potential. Collectively our results suggest that DCA-CF is an effective strategy to prevent IBD in 'Rocha' pear. On the contrary, the DCA-EtOH is not suitable to prevent the induction of fermentation and IBD development. The results also suggest that the IBD development in 'Rocha' pear is related to fermentative metabolism. Highlights: DCA (chlorophyll fluorescence sensor) (DCA-CF) prevented browning in 'Rocha' pear. Dynamic controlled atmosphere (ethanol sensor) (DCA-EtOH) did not prevent browning. DCA-CF contributed to maintain the fruit antioxidant potential during storage. Browning development in 'Rocha' pear seems intimately related to fermentation.